Nostalgia as a weapon … … and also a way to bring back the dream - Sitas, Ari (New Agenda: SA Journal of Social and Economic Policy, 2024)
Instead of focusing on the elections and the implications of the polling outcome, ARI SITAS suggests we channel our pre-occupation with the past and our recent spate of commemorations of political and economic milestones into revisiting the ‘dream’ and restoring a commitment to hope. The last two years have been all about political nostalgias in South Africa. They were marked by serious commemorative events that emphasised the “possible” that never was: 50 years since the Durban strikes, the spontaneous upsurge there of a black working-class; 40 years since the launch of the United Democratic Front (UDF), the unprecedented popular-democratic movement that challenged apartheid to its core. That was 2023.